Brain Tumors and Electroconvulsive Therapy: A Literature Overview of the Last 80 Years - Buday, Jozef; Albrecht, Jakub; Mareš, Tadeas; Podgorná, Gabriela; Horáčková, Klara; Kališová, Lucie; Raboch, Jiri; Anders, Martin (Frontiers in Neurology, 2020)
The safety and efficacy of electroconvulsive therapy (ECT) in patients with a brain tumor has been debated in the past without a clear conclusion. In the last large review published by Maltbie et al. in 1980, it was concluded that the presence of an intracranial mass should be considered an absolute contraindication to ECT. In our updated review we investigated a total of 33 published and indexed case reports, case reports series and reviews of 75 individual patients who underwent ECT in the presence of a brain tumor over the last 80 years. Mounting case reports after the original Maltbie et al. review show that is feasible to apply this method safely in patients with benign or otherwise clinically insignificant lesions. Certain precautionary measures, such as dexamethasone or phenytoin application before ECT, could lead to a further minimalization or even absence of adverse effects, particularly in higher risk individuals.